Pollutant distribution characteristics and microbial response mechanisms in surface and deep brines of the Qaidam Basin - Lu, Xiaohang; Wang, Qiugui; Wang, Zhendong; Ma, Ying; Shi, Zhen; Qi, Delin; Ma, Zhe (Frontiers in Environmental Science, 2025)
This research investigates the distinctions between surface and deep brines in the Salt Lake region of the Qaidam Basin, with an emphasis on their physicochemical properties, organic matter content, heavy metal concentrations, organic pollutants, and microbial community structures. Both surface and deep brine samples were subjected to analysis for total and dissolved organic carbon, heavy metals (specifically Mn, Pb, and Cd), and pollutants, including phthalate esters (PAEs), halogenated compounds, and sulfides. The microbial communities were characterized through high-throughput sequencing, and redundancy analysis (RDA) coupled with correlation heatmaps was employed to evaluate the relationships between pollutants and microbial communities. The findings revealed that surface brines contained higher levels of organic matter, whereas deep brines exhibited significantly elevated concentrations of heavy metals and pollutants. The microbial community composition also varied, with Proteobacteria being predominant in deep brines and Firmicutes in surface brines, along with notable shifts at the genus level. Statistical analyses identified pollutants, particularly Pb, Cd, PAEs, halogenated compounds, and sulfides, as major determinants of microbial community variation. The findings indicate that the accumulation of pollutants in deep brines significantly impacts microbial community structures and ecological functions. Integrating microbial response data into environmental risk assessments is crucial for the sustainable development of deep brine resources in the Qaidam Basin.